Serum levels of IGF-I, IGFBP-3 and colorectal cancer risk: results from the EPIC cohort, plus a meta-analysis of prospective studies. - Rinaldi, S; Cleveland, R; Norat, T; Biessy, C; Rohrmann, S; Linseisen, J; Boeing, H; Pischon, T; Panico, S; Agnoli, C; Palli, D; Tumino, R; et al. (2010)
Several prospective studies have shown a moderate positive association between increasing circulating insulin-like growth factor-I (IGF-I) levels and colorectal cancer risk. However, the associations were often statistically nonsignificant, and the relationship of cancer risk with IGF-I's major binding protein, IGFBP-3, showed major discrepancies between studies. We investigated the association of colorectal cancer risk with serum IGF-I, total and intact IGFBP-3, in a case-control study nested within the EPIC cohort (1,121 cases of colorectal cancer and 1,121 matched controls). Conditional logistic regression was used to adjust for possible confounders. Our present study results were combined in a meta-analysis with those from 9 previous prospective studies to examine the overall evidence for a relationship of prediagnostic serum IGF-I with colorectal cancer risk. In the EPIC study, serum concentrations of IGF-I and IGFBP-3 showed no associations with risk of colorectal cancer overall. Only in subgroup analyses did our study show moderate positive associations of IGF-I levels with risk, either among younger participants only (and only for colon cancer) or among participants whose milk intakes were in the lowest tertile of the population distribution (RR for an increase of 100 ng/ml = 1.43 [95% CI = 1.13-1.93]). Nevertheless, in the meta-analysis a modest positive association remained between serum IGF-I and colorectal cancer risk overall (RR = 1.07 [1.01-1.14] for 1 standard deviation increase in IGF-I). Overall, data from our present study and previous prospective studies combined indicate a relatively modest association of colorectal cancer risk with serum IGF-I.